AN ANALYSIS OF FIGURATIVE LANGUAGE TRANSLATIONIN GOENAWAN MOHAMAD: PUISI-PUISI PILIHAN - Reni Awaliah Pebriani, - (2008)
This research paper entitled "An Analysis of Figurative Language Translation in Goenawan Mohamad: Puisi-puisi Pilihan" attempted to answer the three questions as follow: what the type of figurative language is mostly used in ten poems of Goenawan Mohamad: Puisi-puisi Pilihan, what the translation method is used by the translator in translating figurative language of poetry (based on Newmark's theory) and what the underlying reason for using such method in translating the work. In conducting this research, the researcher used descriptive method. The data were 50 sentences that contain figurative language. The research finding showed that there were six figurative languages found in ten poems of Goenawan Mohamad: Puisi-puisi Pilihan. Metaphor is the most frequent figurative language used by the poet or SL writer, the reason is that probably the poet intended to hide the real meaning of what it conveys. In terms of the method used, word-for-word translation is the most frequent method of translation applied by the translator since the translator attempted to maintain the word order of the source language and the words are translated into their most common meaning. The underlying reason of using word-for-word translation is that the translator apparently intended to keep faithfulness to the original text.